Development policy: theory and practice - Papanek, Gustav Fritz; Harvard University (Cambridge: Harvard University Press, 1968)
This publication comprise studies based on the work of the Development Advisory Service, and written under the auspices of the Center for International Affairs, Harvard University
Includes bibliographical footnotes.
lje 03/09/2018
Loans
Keywords: Economic development